Gegenwart und Zukunft einer Illusion: Rotgrün und die Möglichkeiten gegenwärtiger Politik - Narr, Wolf-Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
The new “red-green” german government, was accompanied by a lot of hope and expectations, which were frustrated in the meanwhile. The article argues, that many of the expectations were “false” and investigates how this could be. Furthermore the fundamental limitations of every “alternative” politics in capitalist society are analyzed.